PENGARUH PENDEKATAN SAINTIFIK DAN GAYA BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAMDI MADRASAH TSANAWIYAH MESRAKOTA PEMATANGSIANTAR - Mul Iadi (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
The purpose of this study was to find out: (1) differences in AkidahAkhlak learning outcomes of students taught with scientific approacheswith students taught with contextual approaches, (2) differences inlearning outcomes Akidah Akhlak students who have visual, auditory andkinesthetic learning styles, and (3) the influence of the scientific approachand student learning styles on the learning outcomes of Akidah Akhlak.This research method is quasi-experimental with the population of thisstudy are students of class VII (Seven). The sample was chosen into twoclasses with cluster random sampling technique, in this case selected forthe experimental class with a scientific approach is class VIIa with thenumber of students 31, while for the control class that is the contextualapproach is class VIId with the number of students 34. Instruments of datacollection is a questionnaire and test of learning outcomes. The techniqueby analysis of variance (Anava) at "α" = 0.05. The results of this study are:(1) student learning outcomes taught with scientific approach (= 33.5)higher than student learning outcomes taught with contextual approaches(= 28,7), with Fcount = 68,10> Ftable = 3.988 , (2) student learningoutcomes with visual learning style (= 34.21) higher than student learning outcomes with kinesthetic learning styles (= 28.38) and auditory learning styles (= 27.69), with Fcount = 79,32 > Ftable = 3.988. And (3) there is aninteraction between learning strategies and learning styles towardslearning outcomes with statistical calculations known F count = 30,16>Ftable = 3.988. Further test calculations using the Scheffe test also showeda significant difference between student learning outcomes taught by thescientific approach and the contextual approach (CTL) as well as studentlearning outcomes with visual, auditory and kinesthetic learning styles.